Marginal Microleakage of Low-shrinkage Composite Silorane in Primary Teeth: An In Vitro Study - Hamid Reza Poureslami; Fatemeh Sajadi; Maryam Sharifi; Shahram Farzin Ebrahimi (Tabriz University of Medical Sciences, 2012)
Background and aims. Despite the increasing demand for adhesive restorations in pediatric dentistry, polymerization shrinkage and subsequent marginal microleakage remains a problem. The aim of this study was to evaluate of the sealing ability of novel low-shrinkage composite silorane in class V cavity of primary canines in comparison with three types of composite resin. Materials and methods. Ninety-one non-carious extracted primary canines were randomly divided in six groups (n=15). Standard class V cavities were prepared on the buccal surface of each tooth that the occlusal margin was in the enamel and the cervical margin extending 1 mm below the cemento-enamel junction. The preparations were restored with the different composite materials in normal consistency with application the bonding in six groups (Filtek silorane; etch + Filtek Silorane; Z250; Filtek supreme; els saremco; Aelite LS). Teeth were then exposed to thermal cycles (1000 cycles, 5°C and 55°C), sealed and immersed in a 0.5% basic fuchsine for 24 hours, and finally sectioned. Buccolingual and marginal leakage was assessed with dye penetration. Results. The best seal were obtained with etch + Filtek Silorane (P < 0.05) and the weakest seal with Z250 composite restorations (P > 0.05). Except for etch + silorane, there was no significant differences in sealing ability (P > 0.05), and in the microleakage degree at the cementum and enamel margins (P > 0.05) between the groups. Conclusion. According to the results, low-shrinkage silorane composite restorations with etching the cavity provide the highest seal in primary teeth.